Stress-Induced CXCR4 Promotes Migration and Invasion of Ewing Sarcoma - Krook, Melanie A.; Nicholls, Lauren A.; Scannell, Christopher A.; Chugh, Rashmi; Thomas, Dafydd G.; Lawlor, Elizabeth R. (Molecular cancer research, 2014)
Ewing sarcoma is the second most common bone cancer in pediatric patients. Although the primary cause of death in Ewing sarcoma is metastasis, the mechanism underlying tumor spread needs to be elucidated. To this end, the role of the CXCR4/SDF-1a chemokine axis as a mediator of Ewing sarcoma metastasis was investigated. CXCR4 expression status was measured in primary tumor specimens by immunohistochemical staining and in multiple cell lines by quantitative reverse transcriptase PCR and flow cytometry. Migration and invasion of CXCR4-positive Ewing sarcoma cells toward CXCL12/SDF-1a were also determined. Interestingly, while CXCR4 status was disparate among Ewing sarcoma cells, ranging from absent to high-level expression, its expression was found to be highly dynamic and responsive to changes in the microenvironment. In particular, upregulation of CXCR4 occurred in cells that were subjected to growth factor deprivation, hypoxia, and space constraints. This upregulation of CXCR4 was rapidly reversed upon removal of the offending cellular stress conditions. Functionally, CXCR4-positive cells migrated and invaded toward an SDF-1a gradient and these aggressive properties were impeded by both the CXCR4 small-molecule inhibitor AMD3100, and by knockdown of CXCR4. In addition, CXCR4-dependent migration and invasion were inhibited by small-molecule inhibitors of Cdc42 and Rac1, mechanistically implicating these Rho-GTPases as downstream mediators of the CXCR4-dependent phenotype. Implications: This study reveals the highly plastic and dynamic nature of CXCR4 expression in Ewing sarcoma and supports a model in which stress-induced upregulation of CXCR4 contributes to tumor metastasis to lung and bone marrow, which express high levels of SDF-1a. Mol Cancer Res; 12(6); 953–64. ©2014 AACR.